Collective bargaining structure and its determinants: an empirical analysis with British and German establishment data - Claus Schnabel; Stefan Zagelmeyer; Susanne Kohaut (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2005)
Using two nationally representative establishment data sets, this paper investigates collective bargaining coverage and firms' choice of governance structures for the employment relationship in Britain and in (western and eastern) Germany. Both countries have experienced a substantial decline in collective bargaining coverage in the last decades. While bargaining coverage is generally lower in Britain, single-employer bargaining is relatively more important in Britain, whereas multi-employer collective bargaining clearly dominates in Germany. Econometric analyses show that more or less the same set of variables play a statistically significant role in explaining the structure of collective bargaining in both countries. These include establishment size, establishment age, foreign ownership, public sector affiliation and being a branch plant.
Keywords: J50; 330; Tarifverhandlungen - internationaler Vergleich; Tarifautonomie; Tarifpartner; Tarifvertrag; Tarifverhandlungen - Determinanten; Betriebsvereinbarung; Flächentarifvertrag; Dezentralisation; IAB-Betriebspanel; Unternehmensgröße; Betriebsgröße; Wirtschaftszweige; Arbeitsbeziehungen; Unternehmenspolitik; Unternehmensführung; Unternehmensalter; öffentlicher Dienst; ausländische Arbeitgeber; regionaler Vergleich; Firmentarifvertrag; Bundesrepublik Deutschland; Großbritannien; Ostdeutschland; Westdeutschland; Tarifpolitik; Schätzung; Großbritannien; Deutschland